Analisis Potensi Objek Wisata Benteng Marlborough Melalui Penerapan Sapta Pesona di Kota Bengkulu - Yanmesli; Dwiatikah, Iklil Nadiah; Sitompul, Laura Meilisa (Jurnal Georafflesia : Artikel Ilmiah Pendidikan Geografi, 2025)
This study analyzes the tourism potential of Marlborough Fort in Bengkulu through the implementation of Sapta Pesona. This fort has unique historical and architectural attractions, supported by adequate amenities and good accessibility. However, the facilities and infrastructure of souvenir shops and tour guides need to be improved. The implementation of Sapta Pesona shows good aspects of "Safe", "Clean", "Cool", and "Beautiful", but the aspects of "Orderly" (visitor compliance) and "Friendly" (friendliness of officers) still need to be improved. The aspect of "Memories" is quite good with local cuisine, but is constrained by the understanding of QRIS payments. This study is expected to provide suggestions for managers and related parties to improve the quality of tourism in the area, such as providing clearer digital information, training officers, and diversifying souvenir products.